Morphogenesis of Bacteriophage φ80: Identification of the Cistron 13 Product - Deeb, Samir S. (1972)
An in vitro complementation reaction leading to the assembly of bacteriophage φ80 tails from component proteins is described. Tail assembly occurs when a lysate of any mutant in cistron 13 is mixed with a second lysate of a mutant in any of the other cistrons involved in tail formation. Lysates of mutants that are blocked in tail formation contain phage heads that can unite with free tails to form infective particles. The rate of the complementation reaction shows little dependence upon temperature, suggesting that the assembly depends largely upon the kinetic encounter of the interacting components. The tail component missing in cistron 13 mutant lysates was purified approximately 55-fold and shown to be, at least in part, a protein having a molecular weight of approximately 22,000. This protein was also released from highly purified infective φ80 particles after osmotic shock followed by heattreatment, suggesting that it most probably is an integral structural protein of the phage tail. Lysates of mutants of bacteriophage λ that are defective in tail formation were shown to contain a tail component identical with or similar to the φ80 cistron 13 product.